2013
DOI: 10.1111/anae.12419
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a modified propofol equilibration rate constant (ke0) on the effect‐site concentration at loss and recovery of consciousness with the Marsh model

Abstract: SummaryThis study compared the predicted effect-site concentration of propofol at loss and recovery of consciousness when using target-controlled infusion devices with the same pharmacokinetic model (Marsh) but a different plasma effect-site equilibration rate constant (k e0 ), the Diprifusor TM (k e0 0.26 min À1) and Base Primea TM (k e0 1.21 min À1). We studied 60 female patients undergoing minor gynaecological surgery under general anaesthesia. Although the total dose of propofol and time until loss of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…A similar pattern of change in bias with the Schnider model was seen in a previous study in which propofol was given by continuous infusion [13]. This observation has important implications in the interpretation of studies that have attempted to compare predicted effect-site concentrations (Ce CALC ) at induction and recovery [14][15][16]. These studies derive Ce CALC as a convolution of Cb CALC with the disposition function of the effect site with a particular k e0 value and make the assumption that any bias in a particular model is similar at times of induction and recovery.…”
Section: Discussionsupporting
confidence: 70%
“…A similar pattern of change in bias with the Schnider model was seen in a previous study in which propofol was given by continuous infusion [13]. This observation has important implications in the interpretation of studies that have attempted to compare predicted effect-site concentrations (Ce CALC ) at induction and recovery [14][15][16]. These studies derive Ce CALC as a convolution of Cb CALC with the disposition function of the effect site with a particular k e0 value and make the assumption that any bias in a particular model is similar at times of induction and recovery.…”
Section: Discussionsupporting
confidence: 70%
“…They found that, with fast k e0 s of 0.45 min À1 with the Schnider model and 1.21 min À1 with the Marsh model, Ce CALC values after a rapid infusion were greater than those observed after a slow infusion, whereas the opposite was seen with the slower k e0 of 0.26 min À1 using the original Marsh model. Similar results were obtained in another study with the Marsh model and a k e0 of 0.26 min À1 [19] and a marked difference in predicted effect site concentrations at loss of consciousness was seen with the Marsh model and k e0 s of 0.26 min À1 or 1.2 min À1 [20]. The results of our simulations of the two infusion rates used (Table 4) replicate the results with the model/k e0 combinations studied in the original study of Sepulveda.…”
Section: Discussionsupporting
confidence: 86%
“…Return of consciousness from general anaesthesia is achieved when the effect‐site concentration of the anaesthetic agent decreases below its therapeutic range . During this process, providing additional stimulation can facilitate return of consciousness , so anaesthetists routinely call the patient loudly or use physical stimulation during emergence from anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Eye opening is commonly used to assess a patient's responsiveness and return of consciousness during emergence from general anaesthesia . However, although patients first open their eyes when responding to a verbal command, they may be in a transitional state between consciousness and unconsciousness rather than in a fully awake state , so they commonly become unresponsive and unconscious again after first opening their eyes.…”
Section: Discussionmentioning
confidence: 99%